A new species of gall midge (Diptera: Cecidomyiidae) feeding on Solanum in Australia. Issue 1 (2nd January 2018) - Kolesik, Peter; Hall, Casey R.; Kitching, Roger L.; Adair, Robin J.
ABSTRACT: Solanum inaequilaterum is a perennial shrub, endemic to the evergreen subtropical rainforest of southern Queensland and northern New South Wales, Australia. An undescribed species of gall midge (Diptera: Cecidomyiidae) was found to cause numerous round hairy galls on leaves, leaf stalks and stems. The new species is described and named Dasineura inaequilaterae Kolesik sp. nov. It is the first Dasineura known to feed on a host plant from the family Solanaceae worldwide.